Urban Infrastructure Finance From Private Operators : What Have We Learned From Recent Experience ? - Annez, Patricia Clarke, 1952- 1952- (The World Bank, 2006)
The author examines the role of private participation in infrastructure (PPI) in mobilizing finance for key urban services, that is, urban roads, municipal solid waste management, and water and sanitation since the early 1990s when private participation came to be seen as a key element in infrastructure development. Her review indicates that for financing urban services, PPI has disappointed-playing a far less significant role than was hoped for, and which might be expected given the attention it has received and continues to receive in strategies to mobilize financing for infrastructure. Looking beyond the number, the author examines transactions and finds that there are good reasons-practical, political, economic and institutional-for these disappointments. Recommending that cities in developing countries try harder is not likely to relieve all these constraints. Experience shows that there are a number of features that raise the risk profile of urban infrastructure for private investors, which has meant that the bulk of the transactions that have taken place have been exceptions rather than harbingers of a growing trend. Many of the measures that could reduce the risk profile are outside the control of many cities, others unlikely to change, and yet another group of steps to be taken that would improve prospects for urban service provision, whether in the hands of public or private operators. These findings suggest a more pragmatic and selective approach to the focus on PPI as a source of finance, and more focus on the array of some of the fundamental steps, among them strengthening the public finances of cities to improve both the capacity to deliver services and to reduce the risks that private investors must take when they invest in urban infrastructure